Two new species of the genus Pison Jurine (Hymenoptera: Crabronidae) from China, with a key to the Chinese species - Li, Tingjing; Li, Qiang (Zootaxa, 2011)
Two new species, Pison irramulus n. sp. from Yunnan, China, and Pison liupanshanense n. sp. from Ningxia, China, are described. A key to the species of Pison from China is provided, along with illustrations of the new species. Type specimens of the new species are deposited in Yunnan Agricultural University.